Compartmentalized Microhelices Prepared via Electrohydrodynamic Cojetting. Issue 6 (19th April 2018) - Gil, Manjae; Moon, Seongjun; Yoon, Jaewon; Rhamani, Sahar; Shin, Jae‐Won; Lee, Kyung Jin; Lahann, Joerg
Abstract: Anisotropically compartmentalized microparticles have attracted increasing interest in areas ranging from sensing, drug delivery, and catalysis to microactuators. Herein, a facile method is reported for the preparation of helically decorated microbuilding blocks, using a modified electrohydrodynamic cojetting method. Bicompartmental microfibers are twisted in situ, during electrojetting, resulting in helical microfibers. Subsequent cryosectioning of aligned fiber bundles provides access to helically decorated microcylinders. The unique helical structure endows the microfibers/microcylinders with several novel functions such as translational motion in response to rotating magnetic fields. Finally, microspheres with helically patterned compartments are obtained after interfacially driven shape shifting of helically decorated microcylinders. Abstract : Anisotropically compartmentalized microhelices are prepared using a modified electrohydrodynamic cojetting technique. The fiber provides unique feature, functions, and an opportunity for biomimicking. The surface of the nanofiber can be selectively functionalized using diverse materials such as magnetic particles. In addition, the helical nanofiber is chopped by cryosectioning to generate the patterned microcylinder and particle.